Os reflexos do novo Código de Processo Civil brasileiro - Santana, Yves Sammy Lopes (2017)
The New Code of Civil Procedure brought changes into the Brazilian legal system. Being a broad theme, we seek to focus the study on the reflexes of the New Code regarding the Consumer Law and, in particular, on its limits to the compensation of moral damages. We began the inaugural chapter dealing with the perspective of moral damage in Brazilian law and consolidated its idea with similarities and considerations when compared to Portuguese law. During the development of the subject, we made brief considerations about the New Code of Civil Procedure and we showed its spirit that seeks the speed and efficiency of the process when implementing procedural means to achieve this goal. Made this consideration, we approached the impact of the New Code in the general framework in the field of Consumer Law, a special part of our study. In sequence, we’ve seen that one of the amendments concerns the limits of moral damages in our law and then we’ve analyzed whether the effect of these changes would be an added value to the consumer or generate mitigation of their rights. Thus, we have developed the subject to come to the conclusion of this present study, that can be seen in parts throughout its development and, in particular, in its final conclusion. In this way, we invite readers to study this topic that has a significant social interest.